Virtual screening, molecular docking, molecular dynamics, and MM-GBSA approaches identify prospective fructose-1,6-bisphosphatase inhibitors from pineapple for diabetes management - Hossain, Md. Sanower; Roney, Miah; Mohd Yusri, Mohd Yunus; Jun Haslinda, Shariffuddin (Taylor & Francis, 2023)
Diabetes affects millions globally and poses treatment challenges. Targeting the enzyme fructose-1,6-bisphosphatase (FBPase) in gluconeogenesis and exploring plant-based therapies offer potential solutions for improving diabetes management while supporting sustainability and medicinal advancements. Utilizing pineapple (Ananas comosus L. Merr.) waste as a source of drug precursors could be valuable for health and environmental care due to its medicinal benefits and abundant yearly biomass production. Therefore, this study conducted a virtual screening to identify potential natural compounds from pineapple that could inhibit FBPase activity. A total of 112 compounds were screened for drug-likeness and ADMET properties, and molecular docking simulations were performed on 20 selected compounds using blind docking. The lead compound, butane-2,3-diyl diacetate, was subjected to 100 ns MD simulations, revealing a binding energy of −5.4 kcal/mol comparable to metformin (−5.6 kcal/mol). The MD simulation also confirmed stable complexes with crucial hydrogen bonds. Glu20, Ala24, Thr27, Gly28, Glu29, Leu30, Val160, Met177, Asp178, and Cys179 were identified as key amino acids that stabilized the human liver FBPase-butane-2,3-diyl diacetate complex, while Tyr215 and Asp218 played a crucial role in the human liver FBPase-Metformin complex. Our study indicates that the lead compound has high intestinal solubility. Therefore, it would show rapid bloodstream distribution and effective action on the target protein, making butane-2,3-diyl diacetate a potential antidiabetic drug candidate. However, further investigations in vitro, preclinical, and clinical trials are required to thoroughly assess its efficacy and safety.